Total soil nutrients drive the enhancement of ecosystem multifunctionality as the succession progresses of the poplar-birch secondary forest - Ma, Dongxu; He, Jiaying; Liu, Qiang; Zhang, Zhidong; Fu, Lihua; Pang, Yue; Tian, Jing; Kong, Deshuo (Frontiers in Plant Science, 2026)
Ecosystem multifunctionality(EMF) refers to an integrated measure of an ecosystem's capacity to perform multiple co-occurring functions. However, change the multi-factor driving mechanism of EMF during poplar-birch secondary forest succession are still poorly understood. Using a space-for-time substitution approach, this study examined four succession stages (early, middle, middle-late, and late) of poplar-birch secondary forests in the Northern Hebei Mountains. It investigated soil physicochemical properties, plant productivity, quantified functional indices and explored the multi-factor driving mechanisms for changing EMF. The results showed that stand and litter (stand volume, litter biomass, litter carbon stock), soil nutrients (organic matter, total nitrogen, available nitrogen, available phosphorus) and soil enzymes (cellobiohydrolase, dissolved organic carbon, n-acetyl-β-D-glucosaminidase and leucine aminopeptidase) significantly elevated as the succession progressed (p < 0.05). Compared with the early stage, the carbon, nitrogen, and phosphorus function indices and the ecosystem multifunctionality index significantly increased by 169%, 287%, 210% and 216% (p < 0.05), respectively. Structural equation modeling (SEM) indicated that increased litter biomass enhanced total soil nutrients, which in turn stimulated soil enzyme activity, ultimately promoting EMF as succession advanced. Notably, total soil nutrients were key factors driving ecosystem multifunctionality enhancement. Overall, plant productivity and soil fertility increased during secondary forest succession, thereby strengthening ecosystem multifunctionality, which provided scientific support for the sustainable development of forest EMF.